Habitat Conversion by Native Spartina Highlights the Importance of Wetland Restoration Design Relative to Site-Specific Vertical Range of Vegetation - Rachel S. Smith; Emily Blair; Andres Deza; Justin C. Hoesterey; David Huang; Russell Johnston; Henry M. Page; Stephen C. Schroeter; Morgan Tusa; Denise Weisman; Kathryn M. Beheshti (Estuaries and Coasts, 2025)
Native vegetation is planted in wetland restoration projects to supplement natural recruitment and achieve a habitat mix that supports ecological functioning. The native cordgrass Spartina foliosa —an ecosystem engineer with a wide elevation range—is frequently planted in wetland restorations in Southern California to jumpstart low marsh development. Although plantings can increase vegetation cover, planted S. foliosa can also convert areas designed as tidal creeks or mudflat to salt marsh, hindering progress towards restoration objectives. At the restored San Dieguito Wetlands (SDW) in Southern California , S. foliosa was planted during (2008–2009) and after wetland construction (2011–2018). In 2023, S. foliosa occupied 10.8 ha at SDW, but had converted 42% of built tidal creek and mudflat habitat to salt marsh. Genetic testing ruled out potential hybridization with non-native Spartina . Tidal creek elevations were higher at SDW than at other California wetlands, overlapping with the design elevation of low marsh for the site. Spartina foliosa extended to lower elevations at SDW than other California wetlands, overlapping with the design elevation of mudflat for the site. Thus, habitat conversion at SDW was likely due to insufficient excavation of built tidal creeks and the lower than expected elevation range of S. foliosa at the site. Much of the existing tidal creek and mudflat habitat at SDW is likely susceptible to habitat conversion to salt marsh. Our results emphasize the need to consider the design elevation of restored habitats relative to site-specific elevation ranges of target wetland species.